Prevalence of hypertension in an urban area: a community-based survey in Trichy, Tamilnadu, India - Gani, Parveen; K, Josephine Priya; Paramasivam, Selvam (International Journal Of Community Medicine And Public Health, 2017)
Background: India is facing an epidemic of non-communicable diseases. Hypertension is now a disease of prime concern due to the mortality and morbidity associated with it. In order to effectively deal with this problem we must first understand the characteristics of this disease. Aims: To assess the prevalence of hypertension in an urban district in Tamilnadu and to study selected risk factors associated with it. Methods: Community based survey in Trichy district of Tamilnadu. A total of 373 individuals were screened in the field practice area of KAP Viswanatham Government Medical College. A proforma was used to collect demographic characteristics and record findings. Blood pressure was measured; BMI and waist-hip ratio were calculated. Statistical Analysis Used: Data were analyzed using SPSS version 20. Descriptive statistics, Chi-square test and unpaired (two sample) t-test were used to study the variables. Results: Prevalence of hypertension was found to be 30.56% and prehypertension was found to be 23.32%. 35.9% patients were overweight/ obese. There was no significant difference between the blood pressures of males and females. Persons above 30 years of age had significantly higher systolic (p<0.001) and diastolic blood pressures (p=0.03) as compared to younger age groups. Conclusions: The prevalence of hypertension is found to be high. We must implement effective screening programmes so as to initiate treatment in the pre hypertensive stage and reduce the burden of disease. Widespread health education programmes need to be implemented to improve awareness regarding modifiable cardiovascular risk factors.